Cerebral venous sinus thrombosis with meningitis in a child with disseminated staphylococcal disease - Shalu Gupta; Sanya Chopra (Wolters Kluwer Medknow Publications, 2021)
The availability of anti-staphylococcal antibiotics today has revolutionized the treatment strategies to fight Staphylococcus aureus. However, its virulent nature still remains a major cause of morbidity and mortality, especially in the pediatric age group. It presents with a wide spectrum of illnesses ranging from minor skin and soft-tissue infections to fatal necrotizing pneumonia and disseminated disease. However, its presentation as meningitis with septic venous sinus thrombosis in pediatrics remains a rare complication till date. We present the case of an 8-month-old girl child with disseminated staphylococcal disease (DSD) caused by community-acquired methicillin-sensitive S. aureus and complicated by acute mastoiditis, meningitis, and cerebral venous sinus thrombosis. This rare and severe manifestation of DSD was managed successfully with intravenous antibiotics and systemic anticoagulation.